PROBLEMATIKA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM (PAI QUR-ANY) DI SMA PRIMAGANDA JOMBANG - Maskhuroh, Lailatul (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2019)
The learning process that is carried out is inseparable from the gap, because every learning cannot be avoided from obstacles and problems. And curriculum development in PAI learning in Primaganda High School using PAI Qur’any includes learning to read al-Qur'an, Translation Science, Sorof Science, Nahwu Science, Al-Qur'an Law Verses. Islamic Religious Education Learning (PAI Qur’any) at Primaganda High School, including: planning, implementing, and evaluating PAI learning. Problems in Learning Islamic Religious Education at Primaganda Jombang High School, among others: Student input is different and students are added regularly, Lack of teacher's jihad spirit and determination to bridge between students and existing facilities, Lack of teaching style of some teachers, making learning devices for learning the Qur'an package has not been realized properly, and so forth. Steps in overcoming students' problems in PAI learning, namely approaching students personally, conducting classifications of students who can and cannot, with peer tutoring learning, where students who are longer teaching new students entering school, etc.